Distribution and Diversity of AM Fungi in the Rhizospheric Soils of Naturally and Artificially Growing Aquilaria malaccensis Lamk. Trees in Arunachal Pradesh and Assam States of North East India - TABIN, TASSO; SHRIVASTAVA, KARUNA; SHUKLA, A. K. (Indian Journal of Hill Farming, 2015)
An investigation was conducted in five locations of Aquilaria malaccensis Lamk. growing areas of Arunachal Pradesh and Assam, north-eastern India to determine distribution and diversity of symbiotic arbuscular mycorrhizal (AM) fungi in relation to physico-chemical properties of rhizospheric soil. The results showed a well distributed (qualitatively and quantitatively) AM fungal associates in the soils supporting A. malaccensis trees as well as in their roots. Chemical properties of soils reveal that all the locations were moderately acidic in nature. The soil samples from naturally grown sites in Golaghat, Assam were recorded with highest in moisture content (22.5%) and nitrogen (3.21%) percentage whereas lowest in phosphorus (0.54%) and potassium (25.9 ppm) contents however, association of maximum number of AM spores 887/100g of soil as compare to commercially cultivated location of Hojai, Assam with average physico-chemical properties harbouring minimum number of AM spores (448)/100g of soil. A total of 20 known different AM fungal species belonging to five genera viz; Acaulospora (2 species), Gigaspora (3 species), Glomus (10 species), Sclerocystis (2 species) and Scutellospora (1 species) were recorded with few unknown genera. Glomus species was most dominating species, of which G. fasciculatum individually contributed the maximum percentage (15.3%) of the total AM fungi recorded during the whole study period. Similarly, AM fungal colonization in roots were also maximum in the natural forest of Golaghat (92.80%) as compare to Nirjuli A (81.60%), Nirjuli B (74.40%) and Itanagar (52.80%) whereas recorded lowest in plantations of Hojai (42.40%) in AM root colonisation of A. malaccensis. Presence or absence of AM hyphae, arbuscules and vesicle in the root samples varied with area to area. The Jaccard index of similarity was high in sites located geographically in different region [Itanagar to Golaghat (0.421) & Hojai (0.433)] while same site and region has much lower. The percentage contribution of AM families, Simpson’s dominance and Shannon diversity index were calculated as highest in Glomeraceae as compared to other families.